2017
DOI: 10.1016/j.xphs.2017.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nonlinear Pharmacokinetics of a Highly Albumin-Bound Compound: Contribution of Albumin-Mediated Hepatic Uptake Mechanism

Abstract: The cause of nonlinear pharmacokinetics (PK) (more than dose-proportional increase in exposure) of a urea derivative under development (compound A: anionic compound [pKa: 4.4]; LogP: 6.5; and plasma protein binding: 99.95%) observed in a clinical trial was investigated. Compound A was metabolized by CYP3A4, UGT1A1, and UGT1A3 with unbound K of 3.3-17.8 μmol/L. OATP1B3-mediated uptake of compound A determined in the presence of human serum albumin (HSA) showed that unbound K and V decreased with increased HSA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Additional previous support for TIPBS was seen when measuring the uptake of a highly bound new chemical entity, shown to be an OATP1B3 substrate. CL int increased with increased HSA concentration in transfected human embryonic kidney (HEK293) cells, where the mechanisms hypothesized with the hepatocyte cell surface may not be present, but overexpression of the OATP transporter is present (Fukuchi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Additional previous support for TIPBS was seen when measuring the uptake of a highly bound new chemical entity, shown to be an OATP1B3 substrate. CL int increased with increased HSA concentration in transfected human embryonic kidney (HEK293) cells, where the mechanisms hypothesized with the hepatocyte cell surface may not be present, but overexpression of the OATP transporter is present (Fukuchi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A facilitated uptake process was seen for both compounds, but there was a more dramatic increase in the unbound uptake for pitavastatin, which has a higher affinity for OATP, than for ANS which has a relatively lower affinity for Oatp. The authors hypothesized, “the higher the affinity for the transporter, the more effective is the albumin-mediated enhancement.” Furthermore, when examining the uptake of highly bound new chemical entity, compound A, which was shown to be an OATP1B3 substrate, the unbound clearance increased with increased HSA concentration in HEK293 cells where the mechanisms hypothesized in hepatocytes may not be present, but overexpression of the OATP transporters is (Fukuchi et al, 2017). Ongoing work in our laboratory will continue to test to validity of this hypothesis.…”
Section: Protein Facilitated Uptakementioning
confidence: 99%
“…1 in the presence of plasma or albumin. In another study, it was shown that increased hepatic uptake clearance (V max /unbound K m ) was observed with increasing albumin concentrations, and this phenomenon was explained by albumin-facilitated uptake (Fukuchi et al, 2017). Although a substantial amount of data have been presented that seems to support this albumin-facilitated uptake hypothesis (Bowman and Benet, 2018), there is still a lot of speculation about the exact mechanism; several hypotheses have been proposed (Poulin et al, 2016;Bowman and Benet, 2018), including the following:…”
Section: Downloaded Frommentioning
confidence: 99%